Translation Technique of English into Indonesian Subtitle in “Bhaijan Bajrangi” Movie - Tira Nur Fitria (ELS Journal on Interdisciplinary Studies in Humanities, 2019)
This objective of the research is to classify the types of translation technique from English to Indonesian subtitle, to determine the most dominant type of translation technique of English to Indonesian subtitle of “Bhaijan Bajrangi” movie. The study of this research used the descriptive qualitative method to describe the subject or the object of the research based on the fact or reality. The data of this research are utterances or sentences in the movie script, which involves two different languages, both the SL (English) and the TL (Indonesian). The source data are “Bhaijan Bajrangi” movie. The data were collected by using the documentation method in the movie. The type of translation techniques used are: 1) Literal (137 data or 28.84 %), 2) Modulation (86 data or 18.11 %), 3) Reduction/Omission (83 data or 17.47 %), 4) Established Equivalence (49 data or 10.32 %), 5) Amplification/Addition (42 data or 8.84 %), 6) Transposition/Shift (33 data or 6.95 %), 7) Borrowing (20 data or 4.21 %), 8) Particularization (12 data or 2.53 %), 9) Generalization (6 data or 1.26 %), 10) Adaptation (5 data or 1.05 %), and 11) Description (2 data or 0.42 %).